Reframing Citizen Participation : Turning Barriers into Guiding Enablers - Abernethy, Päivi; Soini, Katriina; Ommer, Joy; Artell, Janne; Tapiola, Titta; Parodi, Antonio (MDPI, 2025)
Citizen science is increasingly recognized as a potential catalyst for sustainability transitions, climate action, and behavioral change by fostering collaboration between scientists and the public. While it offers benefits such as mutual learning, awareness raising, and improved outcomes, sustaining long-term diverse engagement remains a challenge. Research to date has largely emphasized data outcomes and initial participation, often overlooking the relational, social, and practical dimensions crucial for continued involvement. A disconnect persists between researchers’ data-driven goals and participants’ personal motivations, compounded by insufficient training and institutional support for engagement. This paper presents a novel framework for enhancing citizen engagement, drawing on a state-of-the-art literature review and focus group insights from the H2020 I-CHANGE project. It identifies enablers for and barriers to participation, reframing the latter as opportunities for support. The findings are organized into four themes: (1) call for participation, focusing on intrinsic motivation and local relevance; (2) project design, highlighting inclusive tools and communication; (3) a collaborative process, emphasizing trust, clarity, and support; and (4) participation benefits, including meaning, recognition, and social connection. This study underscores the need to build trust, foster relationality, and align expectations. It proposes practical engagement criteria and calls for deeper exploration of the relational foundations of citizen science.
Keywords: citizen science; barriers; effective engagement; enablers; participation; research design; assessment criteria